PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MASKER WAJAH MUSTIKA RATU (Studi Kasus pada Konsumen Kec. Tembalang Kota Semarang) - Ipa Audina Br Harahap; Wahyu Hidayat (Universitas Diponegoro, 2018)
Beauty care products like a facial masks are an important requirement for women. PT Mustika Ratu which produce facial mask has decreased of sales and decrease Brand Index from 2014-2017. This study focus on the influence of product quality and price on consumer purchasing decision in Tembalang Districts Semarang City. The purpose of this study is to identify the influence of product quality and price on purchasing decision of Mustika Ratu face mask for consumers in Tembalang Districts Semarang City. The type of research is explanatory research. Sampling technique is non probability sampling based on purposive sampling. The number of sample is 100 respondents. The analysis technique used SPSS 16.0. The results of the research showed that the quality of product influence the purchase decision at the amount 21.5%. Price affects the purchasing decision reach to 29.7%. Meanwhile, simultaneously product quality and price influence to purchase decision by donating 35,6%. Based on the calculation of Test F shows that there is a positive influence between product quality and price to purchasing decision. It is means the better the quality of products and consumer perception of prices, the higher purchasing decision Mustika Ratu face mask in Tembalang District Semarang City. In addition, the price has the most dominant influence with regression keofisien value of 0.715. Suggestion in this research is to improve product quality both in packaging, function and diversity of Mustika Ratu face mask product. Moreover in terms of the price, the suitability of the price with the quality and benefits of the product must also be upgraded and improved.